Communication Strategies of the Office of Religious Affairs (KUA) in Preventing Early Marriage: A Case Study of Medan Tuntungan District - Khairiya Wirda Berasa; Suheri Harahap (Pencerah, 2026)
This study aims to analyze the communication patterns of the Medan Tuntungan District Religious Affairs Office (KUA) in preventing early marriage. Early marriage remains a social problem in urban areas, influenced by social, cultural, economic, and religious factors, necessitating effective communication strategies. This study employed a qualitative approach with a descriptive phenomenological design. Data were collected through in-depth interviews, participant observation, and documentation studies with purposively selected informants including the Head of the KUA, religious instructors, community leaders, parents, and adolescents. The results indicate that the Medan Tuntungan KUA implements a multidimensional communication pattern consisting of linear, interactional, and transactional patterns. The linear pattern is used in mass outreach through lectures and counseling, the interactional pattern is applied in dialogical premarital counseling, and the transactional pattern is seen in cross-sector collaboration with schools, community health centers, and community leaders. These three patterns operate simultaneously and complement each other in raising public awareness about the dangers of early marriage. Furthermore, the results also indicate that the rate of early marriage in this area is relatively low. The conclusion of this study confirms that the success of communication to prevent early marriage is influenced by the KUA's ability to build adaptive, participatory, and collaborative communication. The main obstacle identified was limited facilities, but this can be overcome by utilizing community social spaces. This research contributes to the development of development communication and organizational communication studies in the context of preventing social problems.